Psychological Distress and Attachment Insecurity of Stalked Mothers - Wolf, Nele Marie (Journal of interpersonal violence, 2021)
There is a lack of research about intimate partner stalking when victim and stalker have children together. The aim of the current study was to provide knowledge about the mental health status and attachment patterns of mothers stalked by the father of one or more of their children. One hundred ninety six Danish women, recruited via a closed social network for stalked mothers, completed an anonymous online questionnaire concerning their experiences of violence during and after the relationship with the stalker, relationship characteristics, attachment patterns, and psychological distress. Results indicated high exposure to psychological maltreatment during the victim–stalker relationship, harassing and violent stalking behaviors after relationship termination, and high levels of functional disabilities, PTSD (posttraumatic stress disorder), other trauma-related, affective, and somatization symptoms. Furthermore, the women retrospectively reported an increase in attachment insecurity from the time before their relationship with the stalker to the time of study participation (after they experienced relationship violence and/or stalking). Stalking behaviors uniquely contributed to the explanation of the mothers’ psychological distress above the effects of relationship violence. Moreover, attachment insecurity appeared to be the strongest predictor of psychological distress. Having children together with their stalker captures women in an ongoing situation of threat and interpersonal traumatization that differs from other forms of stalking in many respects. The present study is the first drawing attention to the experiences and suffering of stalked mothers, a particularly vulnerable group of stalking victims.